2013
DOI: 10.1371/journal.pone.0059142
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Capsid of Recombinant Adeno-Associated Virus 2 (AAV2) Vectors: The Final Threshold?

Abstract: The ubiquitin-proteasome pathway plays a critical role in the intracellular trafficking of AAV2 vectors, and phosphorylation of certain surface-exposed amino acid residues on the capsid provides the primary signal for ubiquitination. Removal of several critical tyrosine (Y) and serine (S) residues on the AAV2 capsid has been shown to significantly increase transduction efficiency compared with the wild-type (WT) vectors. In the present study, site-directed mutagenesis of each of the 17 surface-exposed threonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
129
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(132 citation statements)
references
References 52 publications
1
129
1
1
Order By: Relevance
“…The rational design of the AAV capsid to avoid proteosomal degradation enhances transduction efficiencies (30,(35)(36)(37)(38). This is accomplished by the substitution of surface-exposed residues that otherwise would be phosphorylated and thereby target the capsid for ubiquitin-dependent proteasomal degradation.…”
mentioning
confidence: 99%
“…The rational design of the AAV capsid to avoid proteosomal degradation enhances transduction efficiencies (30,(35)(36)(37)(38). This is accomplished by the substitution of surface-exposed residues that otherwise would be phosphorylated and thereby target the capsid for ubiquitin-dependent proteasomal degradation.…”
mentioning
confidence: 99%
“…15 We have also described that for the genome-modified AAV2 vectors, LC1 and LC2, in which one of the D-sequences in the viral inverted terminal repeats (ITRs) was deleted, the efficiency of transgene expression from the single-stranded genomes was significantly increased. 17 Thus, as depicted schematically in Figure 1, we generated the following set of QMssAAV2 vectors containing the firefly luciferase (Fluc) reporter gene flanked by either the unmodified ITRs (QM-ssAAV2-WT-Fluc), or with D-sequence-deleted ITRs (QM-ssAAV2-LC1-Fluc and QM-ssAAV2-LC2-Fluc).…”
Section: Resultsmentioning
confidence: 99%
“…By modifying the capsids, we have generated the nextgeneration AAV vectors in which specific surfaceexposed tyrosine (Y), serine (S), threonine (T), and lysine (K) residues were mutagenized, and various permutations and combinations of these mutations thereof, to significantly augment the transduction efficiency of these vectors, both in vitro and in vivo, by circumventing proteasome-mediated degradation. [14][15][16]30 At least one of these vectors has also shown to be less immunogenic 31 and, in a recent phase I clinical trial, shown efficacy for the potential gene therapy of Leber's hereditary optic neuropathy. 32 We have also described strategies involving genome modifications that lead to the generation of ssAAV vectors with which high efficiency of transgene expression can be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A herculean effort by yet another long-term colleague, George Aslanidi, PhD, and colleagues, who mutagenized all 17 surface-exposed serines, all 15 surfaceexposed threonines, and various permutations and combinations thereof, led to the identification of the most efficient AAV2 vectors to date. 7 In addition, because ubiquitination occurs on lysines, all seven surface-exposed lysine residues on the AAV2 capsid were also mutagenized. 8 Remarkably, most, if not all, of the surfaceexposed tyrosine, serine, threonine, and lysine residues are highly conserved among all 10 commonly used AAV serotype vectors.…”
mentioning
confidence: 99%